Oncolytic Effect Of Newcastle Disease Virus On The Mcf-7 And Mda-Mb-231 Breast Cancer Cell Lines - Meyyappan, Narayani (2003)
The study was conducted to find a new anti-cancer agent for the treatment of breast cancer. The oncolytic effect of Newcastle disease virus (NDV) on MCF-7 and MDAMB- 231 breast cancer cell lines was investigated using various methods. The V 4- UPM and AF2240 strains of NDV were propagated in the allantoic fluid of 11-daysold embryonated eggs. The allantoic fluid was harvested, purified and stored at - 20°C. The haemagglutination (HA) test was conducted on the purified viruses to ' determine the HA titre of the V4-UPM and AF2240 strains, which were 16 384 and 128 HA units consecutively. The microculture tetrazo1ium (MTT) assay was carried out to detect the cytotoxic effect of the NDV strains on breast cancer cell lines using monolayer and co-culture techniques to determine the IC50 value. The IC50 values for the MCF-7 treated with V4-UPM strain were 4096 and 128 HA units for the monolayer and co-culture, respectively, while, the MDA-MB-231 had an IC50 value of 96 HA units for both techniques. When treated with AF2240 strain, MCF-7 showed IC50 value of 96 and 64 HA units for the monolayer and co-culture methods, respectively. Whereas, the IC50 value for MDA-MB-231 cells was 4 HA units for both techniques. Further studies were done to observe the ultrastructural changes in the treated cells and viewed under an energy filter transmission electron microscope